Regulation of YAP and Wnt signaling by the endosomal protein MAMDC4. - Christopher M Cox; Meng-Han Wu; Marco Padilla-Rodriguez; Isabella Blum; Samina Momtaz; Stefanie A T Mitchell; Jean M Wilson (PLoS ONE)
Maintenance of the intestinal epithelium requires constant self-renewal and regeneration. Tight regulation of proliferation and differentiation of intestinal stem cells within the crypt region is critical to maintaining homeostasis. The transcriptional co-factors β-catenin and YAP are required for proliferation during normal homeostasis as well as intestinal regeneration after injury: aberrant signaling activity results in over proliferation and tumorigenesis. Although both YAP and β-catenin activity are controlled along canonical pathways, it is becoming increasingly clear that non-canonical regulation of these transcriptional regulators plays a role in fine tuning their activity. We have shown previously that MAMDC4 (Endotubin, AEGP), an integral membrane protein present in endosomes, regulates both YAP and β-catenin activity in kidney epithelial cells and in the developing intestinal epithelium. Here we show that MAMDC4 interacts with members of the signalosome and mediates cross-talk between YAP and β-catenin. Interestingly, this cross-talk occurs through a non-canonical pathway involving interactions between AMOT:YAP and AMOT:β-catenin.